Local control of sphincter‐preserving procedures and abdominoperineal resection for locally advanced low rectal cancer: Propensity score matched analysis. Issue 3 (14th August 2017) - Okamura, Ryosuke; Hida, Koya; Yamaguchi, Tomohiro; Akagi, Tomonori; Konishi, Tsuyoshi; Yamamoto, Michio; Ota, Mitsuyoshi; Matoba, Shuichiro; Bando, Hiroyuki; Goto, Saori; Sakai, Yoshiharu; Watanabe, Masahiko; et al.
Abstract: Sphincter‐preserving procedures (SPPs) for surgical treatment of low‐lying rectal tumors have advanced considerably. However, their oncological safety for locally advanced low rectal cancer compared with abdominoperineal resection (APR) is contentious. We retrospectively analyzed cohort data of 1500 consecutive patients who underwent elective resection for stage II‐III rectal cancer between 2010 and 2011. Patients with tumors 2‐5 cm from the anal verge and clinical stage T3‐4 were eligible. Primary outcome was 3‐year local recurrence rate, and confounding effects were minimized by propensity score matching. The study involved 794 patients (456 SPPs and 338 APR). Before matching, candidates for APR were more likely to have lower and advanced lesions, whereas SPPs were carried out more often following preoperative treatment, by laparoscopic approach, and at institutions with higher case volume. After matching, 398 patients (199 each for SPPs and APR) were included in the analysis sample. Postoperative morbidity was similar between the SPPs and APR groups (38% vs 39%; RR 0.98, 95% CI 0.77‐1.27). Margin involvement was present in eight patients in the SPPs group (one and seven at the distal and radial margins, respectively) and in 12 patients in the APR group. No difference in 3‐year local recurrence rate was noted between the two groups (11% vs 14%; HR 0.77, 95% CI 0.42‐1.41). In this observational study, comparability was ensured by adjusting for possible confounding factors. Our results suggest that SPPs and APR for locally advanced low rectal cancer have demonstrably equivalent oncological local control. Abstract : In this multicenter cohort study of 794 patients whose tumors were within 5 cm from the anal verge, propensity score matched analysis showed that resection margin involvement and incidence of local recurrence were similar between sphincter‐preserving procedures and abdominoperineal resection. Sphincter‐preserving procedures have recently progressed. They are oncologically useful options even for locally advanced low rectal cancer.